Development of Non-Fiction Text Digital Learning Media in Narrative Writing Skills for Fourth Grade Elementary School Students - Wahyu Budi Astutik; Setya Yuwana; Hendratno (IJORER : International Journal of Recent Educational Research, 2021)
This development research was carried out improve the learning outcomes of Indonesian students learning non-fiction text material in narrative writing skills in fourth grade students. This type of research is a Research and Development with Prestest-Posttest One Group Design, using the 4D development model which includes four stages, namely Define, Design, Development and Dissemination. Research respondents of this research are fourth grade. The instrument used a validation questionnaire, observation, practicality questionnaires and learning outcomes tests. Results of this research indicate that the validation of the material obtained 89.4% and the validation of the media obtained 100%. The practicality of the teacher's questionnaire got a percentage of 95%, while the student questionnaire got a percentage of 98.6%, the results of teacher and student observations obtained a percentage of 92.85% and 95%. The effectiveness based on giving pretest and posttest to students totaled 25 students with an average pretest result of 79.52 while the average posttest was 91.96. The result of the t-count is -11.085 and the probability of 0.000 which shows that there is a significant difference in the value of the narrative writing skills of fourth grade elementary school students using the development of non-fiction text digital-based learning media.